Frontiers in RNAi: Volume 1 - Tripp, Ralph A. (Frontiers in RNAi, 2014)
RNA interference (RNAi) is a biological process in which small nucleotide sequences destroy specific mRNA molecules and, therefore, interrupt genetic expression. RNAi has rapidly developed into a widely used technique in biotechnology, experimental biology, genomics and medicine. Frontiers in RNAi is a collection of research articles covering the applications of RNAi principles and technologies and has been compiled by members of the RNAi Global Initiative, a collection of academic and industrial groups with extensive experience in genome-wide RNAi screening. Chapters included in the first volume touch on some of the recent advances in RNAi technology (i.e., applications to 3D cell culture, drug repurposing, and bioproduction) and provide guidance on how to address the continued challenges associated with off-target effects, database structuring, and pooled shRNA screens.